2+(3+6m)7=

Simple and best practice solution for 2+(3+6m)7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+(3+6m)7= equation:


Simplifying
2 + (3 + 6m) * 7 = 0

Reorder the terms for easier multiplication:
2 + 7(3 + 6m) = 0
2 + (3 * 7 + 6m * 7) = 0
2 + (21 + 42m) = 0

Combine like terms: 2 + 21 = 23
23 + 42m = 0

Solving
23 + 42m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-23' to each side of the equation.
23 + -23 + 42m = 0 + -23

Combine like terms: 23 + -23 = 0
0 + 42m = 0 + -23
42m = 0 + -23

Combine like terms: 0 + -23 = -23
42m = -23

Divide each side by '42'.
m = -0.5476190476

Simplifying
m = -0.5476190476

See similar equations:

| 38=a-28 | | (9x^2-7x+65)-(11x+8x^2)= | | 8x+4-3x+2=41 | | 8m+3=16 | | f(x)=ln(8x) | | 25a-8b+4c-6a+13b-c= | | 2a+12+a+(3a-9)=117 | | 6-18=m-4+14 | | (-3x^2-2x-2)+(2x^2+4x+4)= | | 9p-4p=-7 | | 27=3/7+6 | | 9x-4=65 | | 6+c=18 | | 3w+15=-4(w-2) | | 3w+15=-(w-2) | | 5-(1-x)=20 | | 7x+5y=-16 | | x=3(y/9) | | (4x^2+3x-5)(2x^3-10x+11)= | | 6x-15=6x | | 2x+7=10x+9 | | a-4/9a=-7/9 | | 1/2x^3-1/2x^2-24=0 | | 7=-2n-5 | | p(x)-750x^2+15000x=0 | | 0.8(25m-20n)= | | 5(2n-1)=5 | | -6+2t=3t-(6+5) | | 3x=y/9 | | ((d-4)/4)^2=49 | | -102=-6(8n+1) | | 2(3-6n)=102 |

Equations solver categories